THE EFFECTIVENESS OF INFORMATION SERVICES USING THE PROJECT BASE LEARNING METHOD TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT SMP NEGERI 9 MEDAN - Nufus Adlina, Cut Raisyah (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to determine the profile of Pancasila students at SMP Negeri 9 Medan. The purpose of this research is to describe the differences in scores in character development through the experimental group Pancasila student profile program before and after being given information service treatment using the Project Base Learning method. Meanwhile, the control group was given treatment before and after being treated with information services without the project based learning method. This research is quantitative research with an experimental research type. The object of this research was class VIII students at SMP Negeri 9 Medan. The data collection technique in this research used a questionnaire for students with a Pancasila student profile. The results of this research show that students who have a low Pancasila student profile have bad character and are difficult to be accepted by society. The analysis test results used the Wilcoxon Signed Ranks Test and the Kolmogorov Smirnov Two Independent Samples analysis test. Thus, based on the results of research conducted, among others: (1) there are significant differences in character development through the Pancasila student profile program for students in the experimental group before (pretest) and after (posttest) with information services using the Project Base Learning method. (2) there is a significant difference in character development through the Pancasila student profile program for students in the control group before (pretest) and after (posttest) with information services. (3) there is a significant difference in character development through the Pancasila student profile program for students in the experimental group and the control group who were given treatment.